2020
DOI: 10.1039/d0ta06264b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic covalent bond multiplicity on the performance of vitrimeric elastomers

Abstract: It is still a challenge to integrate multiple dynamic covalent bonds (DCBs) into one network, so the effects of DCBs multi-plicity on the performance of covalent adaptive networks (CANs) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 61 publications
1
33
1
Order By: Relevance
“…As an example, Guan et al reported a covalently crosslinked yet malleable polybutadiene via Grubbs' Ru catalyzed olefin metathesis. 11 Besides, a variety of DCBs, including β-hydroxyl ester bonds, 12,13 imine bonds, 14,15 boronic ester bonds, 16 acetal, 17 and silyl ether, 18 have been researched in elastomer vitrimers.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Guan et al reported a covalently crosslinked yet malleable polybutadiene via Grubbs' Ru catalyzed olefin metathesis. 11 Besides, a variety of DCBs, including β-hydroxyl ester bonds, 12,13 imine bonds, 14,15 boronic ester bonds, 16 acetal, 17 and silyl ether, 18 have been researched in elastomer vitrimers.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demon-strate that epoxy-functionalized SBR could be successfully prepared by introducing GMA during emulsion polymerization of SBR. [41,44,45] Hence, the modification method provides a promising strategy to prepare various kinds of functionalized SBR.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the difficulties in synthesizing polymers with several dynamic covalent bonds and activating different dynamic bonds separately, there are few reports about the interactions between different dynamic covalent bonds in polymeric materials. [31,32] Our group has reported that diselenide bond as one kind of dynamic covalent bond that could be activated under mild visible light irradiation, and then the metathesis reaction will occur. [33,34] The unique activation condition of diselenide bonds should be orthogonal to most of the stimulating conditions of other dynamic covalent bonds.…”
Section: Introductionmentioning
confidence: 99%